Urinary phthalate metabolites associated with increased prevalence of gallstone disease in U.S. adults: data from the NHANES study - Feng Jia; Yu Chang; Yuguang Li; Fangqi Li; Xinqiao Chen; Xiangliang Liu; Wei Li; Jiuwei Cui (BMC Public Health)
Abstract Background Phthalate exposure has been hypothesized to influence cholesterol metabolism and gallstone pathogenesis, but previous studies are limited. We aimed to examine the associations between urinary phthalate metabolites and prevalence of gallstone disease in a nationally representative sample. Methods We analyzed data on 1,696 adults aged ≥ 30 years from the National Health and Nutrition Examination Survey (NHANES) 2017–2018. Gallstone disease was defined based on self-reported physician-diagnosis. Exposure was measured by urinary concentrations of 10 phthalate metabolites. Multivariable logistic regression model was to assess individual exposure-effect associations. Weighted quantile sum (WQS) regression, Quantile g-computation (Qgcomp) analysis and Bayesian kernel machine regression (BKMR) assessed metabolite mixtures in relation to gallstones. Results In the multivariable logistic regression model, compared to the lowest quartile (Q1) of urinary mono (2-ethyl-5-carboxypentyl) phthalate (MECPP), the highest quartile (Q4) was associated with an 82% increased risk of gallstone formation (OR: 1.82, 95% CI: 1.17, 2.85). Similarly, for mono(3-carboxypropyl) phthalate (MCPP), the risk increased by 78% in the Q4 group compared to Q1 (OR: 1.78, 95% CI: 1.02, 3.14). The WQS index exhibited a significant positive association with gallstone prevalence (OR: 1.37, 95%CI: 1.02, 1.84). In the Qgcomp model, four urinary phthalate metabolites, including MECPP, MCPP, mono benzyl phthalate (MBzP) and mono-carboxynonyl phthalate (MCNP), were positively associated with an increased risk of gallstones. BKMR identified exposure-response trends for MECPP, MCPP, and MBzP. Conclusion Higher urinary phthalate metabolite concentrations were associated with increased gallstone risk. These novel findings suggest phthalate exposure may contribute to lithogenic pathogenesis. Future prospective and mechanistic research is warranted.